Direct large-volume injection analysis of polycyclic aromatic hydrocarbons in water (2018)
ABSTRACT:Due to the health risks for both humans and living beings caused by polycyclic aromatic hydrocarbons (PAHs), the monitoring of these compounds in environmental matrices is mandatory. This work proposes an analytical method for analyzing anthracene (AN) and benzo[a]pyrene (BaP), two of the most representative PAHs, at ultra-trace concentrations in water, employing direct injection of large volumes of samples coupled with reversed-phase high-performance liquid chromatography. For this purpose, principal component analysis was used to examine the behavior of AN and BaP within the chromatographic system. Results showed that AN and BaP chromatographic behavior can be described by three models representing their identification, the quantification of AN and that of BaP, respectively. The factors affecting the obtained models, such as the injection volume, column temperature, flow rate, strength of the mobile phase, and the excitation and emission wavelengths, were examined and optimized by means of design of experiments. Finally, the analytical method was validated, obtaining promising limits of detection and quantification. The developed analytical method was demonstrated to be useful for a sensitive analysis of the target analytes in relatively clean natural water matrices.